The development and formation of competition of the market for the products of the sewing and knitting industry - Maksudov, Abdusalam (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The factors of the development of the market of sewing and knitting products and the formation of a competitive advantage are shown in the article. Competition advantage in reaching selectable strategies illuminated.